Study on Implementation of 5S Concept for the Office Performance at Divisional Secretariat, Nintavur (Global Journal of Management and Business Research, 2021)
Divisional secretariats are the public service organization that provides core public services to the public. The public has a close relationship with Divisional secretariat offices since they are dealing with Divisional secretariat offices for obtaining most of the livelihood services. Also, educated and uneducated people are coming to Divisional secretariat offices to obtain their livelihood services. Therefore, the Divisional secretariat offices should maintain on-time, effective, efficient,
Keywords: #x2018; 5S#x2019; system; divisional secretariat; sort; set in order; shine; standardize; sustain